Pemahaman UMKM terhadap Sumber Modal di Lembaga Keuangan Mikro Syariah - Muhammad Adam; Zuhrinal M Nawawi (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2022)
Islamic Microfinance Institutions (LKMS) mean bodies engaged in the financial sector based on Islamic teachings originating from the Qur'an and As Sunnah. Most of the financing for Islamic Microfinance Institutions is intended for the business sector, and has the ability to reach micro-enterprises. This study aims to analyze the awareness and perceptions of Micro and Small Enterprises (MSMEs) in Medan City regarding Capital Sources in Islamic Microfinance institutions. The method used in this study is descriptive quantitative using the Classical Assumption Test formula, namely Normity Test, Multicollinearity, heteroscedasticity . The results of this study indicate that in general the understanding of MSMEs in Medan City regarding sources of capital in Islamic Microfinance Institutions is still low. However, the perception is quite good that among MSME actors they still use Islamic financial institutions in business capital with research questionnaires that are distributed to several communities by answering questions from the questionnaire.